Risk Factors for Early Weight Loss in Breastfed Term Infants: Biomedical Perspective - Tolibin, Restu Triwulandani; Herdhiyanti Siwi, Dinar; Anggitaratri, Zakia Novi (Universitas Muhammadiyah Surakarta, 2025)
Infants can lose some of their birth weight in the first weeks of life. Identification of the risk factors associated with breastfed infant weight loss in the few weeks following the birth can increase the success of exclusive breastfeeding. The aim of this research was to determine the risk factors in breastfed full-term infants that cause early weight loss at a hospital. This study was retrospective study, which analyzes weight loss in breastfed term infants born between July 1, 2024, and October 31, 2024, at hospital in Boyolali, Central Java. A total of 194 infants were included in the study. The variables studied the maternal age, method of delivery, infant’s birth weight, infant’s gender, and maternal parity. Pearson Chi-Square test was used to compar categorical data. Logistic Regression with the Backward Stepwise method was used to analyze multivariate data. Caesarean section was statistically significant risk factor for early weight loss in breastfed term infants that increases the chance of weight loss by 1.56 times. We concluded that caesarean section increased the chance of early weight loss in breastfed term infants.